Pemberdayaan Ekonomi Perempuan di Majlis Ta’lim Yasin Fadhilah Karang Rejo Metro Utara Kota Metro - Ali, Muhammad; Susilawati, Ani; Binhas, Qois Azizah; Eka Priyantoro, Dian; Wahyudi, Dedi; Khotijah, Khotijah (CV. Creative Tugu Pena, 2023)
This research examines about women's economic empowerment at majlis ta'lim Yasin Fadhilah Karang Rejo Metro Utara Metro city. Community empowerment efforts can be done in three ways, namely by strengthening their human resources, protecting the community, and defending weak communities. The purpose of this empowerment is carried out for assistance as well as guidance to the community especially in majlis talim Yasin Fadhilah Karang Rejo North Metro Metro City related to women's economic development. women's economic development. Through home industry small business units have been developed such as making tempeh chips, making cakes, and geribik. In running a business, of course, there are many obstacles faced such as declining selling power due to difficulties in marketing products in the market. in the market. The method used in this research is Participatory Action Research PAR. The results showed that the decline in competitiveness due to weakness in marketing products. Keywords: Economic Empowerment of Women, Economic Empowerment, Assistance Economic Empowerment